Advances in sRNA-mediated regulation of Salmonella infection in the host - He, Ting; Ding, Yonghui; Sun, Yuling; Li, Tiansen (Frontiers in Cellular and Infection Microbiology, 2025)
Salmonella is a foodborne pathogen that enters the host’s body through contaminated food and water, leading to gastroenteritis and systemic diseases. It is a significant veterinary and human pathogen capable of infecting both humans and animals, with substantial impacts on public health, human well-being, and the economic development of the livestock and poultry farming industry. Small non-coding RNAs (sRNAs), typically 50–500 nucleotides (nt) in length, have been identified in various bacteria, including Escherichia coli, Brucella, Pseudomonas aeruginosa, and Salmonella. These sRNAs play crucial roles in regulating diverse physiological processes within bacteria. This review emphasizes recent advances in understanding how sRNAs regulate the virulence of Salmonella spp, such as the discovery of novel sRNAs like SaaS and new regulatory mechanisms of known sRNAs like RyhB-1/RyhB-2 and SdsR/Spot 42. It also outlines critical future directions, including exploring the multifaceted functions of sRNAs in lifestyle or infection phase transitions, fully elucidating their roles in regulating the host immune response, studying the combined actions of multiple sRNAs on host pathogenesis and expanding research to more Salmonella serotypes and diverse animal models. Through these efforts, this review aims to enhance our understanding of Salmonella sRNAs and their infection mechanisms.